New Dalit Assertion and the Rejection of Buffalo Sacrifice in South India - Aya Ikegame (South Asia Multidisciplinary Academic Journal)
Taking a cue from the recent prevention of a buffalo sacrifice to a powerful local goddess in Karnataka and the writings of Dalit activist-turned-spiritual-guru M. C. Raj, this article traces a history of how buffalo sacrifice has been witnessed, described and analyzed from the mid nineteenth to the twentieth century. This endeavor reveals how structural-functionalist understandings of the ritual obscured the voice of Dalit dissent while stressing the organic unity of the village as a whole. This was despite the fact that colonial accounts, relied upon in later studies, clearly documented the reluctance of Dalits to participate. This article also finds within colonial writings an unexpected description of Dalits as original inhabitants of the land, an idea that has been revived in contemporary movements of Dalit assertion.